MMP2, MMP9 and TIMP2 polymorphisms affect sperm parameters but not fertility in Polish males. (12th July 2016) - Kurzawski, M.; Kaczmarek, M.; Kłysz, M.; Malinowski, D.; Kazienko, A.; Kurzawa, R.; Droździk, M.
Summary: Proper function of the blood–testis barrier is pivotal to spermatogenesis. Synchronised action of matrix metalloproteinases (MMP) and their inhibitors (TIMP) is mandatory to maintain dynamic balance of the barrier. Therefore, the association of functional genetic variants of MMP‐2, MMP‐9 and TIMP‐2 and male infertility was studied. A total of 416 infertile males and 421 healthy subjects were genotyped for 7 SNPs within MMP2, MMP9 and TIMP2 genes, along with the assessment of semen parameters (concentration, motility and morphology of spermatozoa). No association was observed between the studied genotypes and male infertility. However, higher sperm concentration was associated with TIMP2 rs8080623 C and rs2277698 T variants among infertile men, and with MMP9 rs17576 A minor allele in controls ( p < .05). TIMP2 rs9900972 T and rs2277698 T allele were associated with higher percentage of morphologically normal spermatozoa among controls. MMP2 rs2285053 TT homozygous infertile patients presented higher percentage of spermatozoa displaying nonprogressive motility. Haplotype analysis revealed strong linkage disequilibrium between the studied loci (5 of 8 possible TIMP2 haplotypes, and 3 of 4 possible MMP2 and MMP9 were found). None of the haplotypes showed association with infertility. This study results suggest an association between MMP9 and TIMP2 SNPs with sperm parameters, but not infertility.